Perspective Review of Polymers as Additives in Water-Based Fracturing Fluids - Al-Hajri, S. (American Chemical Society, 2022)
After successful implementation for more than 6 decades by the oil and gas industry, hydraulic fracturing remains the pioneer well stimulation method to date. Polymers are one of the additives in fracturing fluids that play a significant role. Polymers are used as friction reducers and viscosifiers to provide a transport medium for proppants in fracturing fluids. There are many polymer-based fracturing fluid systems, but choosing the most appropriate type and system depends on the type of application and a wide range of parameters. Currently, there is no complete review study that gives a reference and hence a perspective for researchers on the use of polymers in hydraulic fracturing. This paper summarizes the published literature on polymers used in fracturing fluids and discusses the current research issues, efforts, and trends in the field, aiming to provide an overview of the polymer applications in slick-water and cross-linked gel systems. The mechanism and limitation of polymer use such as polymer degradation, fracture conductivity reduction, and polymer adsorption are also reviewed in this paper. The reviewed literature suggested that polymers are important additives in fracturing fluids not only to provide adequate transportation of proppants but also to determine the width of the fracture whereby higher viscosities yield wider fractures. The development of synthetic polymers and associative polymers in fracturing fluids showed a remarkable potential to improve the stability of fracturing fluids in unconventional reservoirs under reservoir conditions, which makes it an interesting topic for future studies. Â© 2022 American Chemical Society. All rights reserved.